Finnish variety of congenital nephrotic syndrome in association with cytomegalovirus infection: Double jeopardy - Shraddha Lohia; Georgeena Elsa Jose; Prahlad D Pote (Wolters Kluwer Medknow Publications, 2021)
Background: The term "congenital" is used for cases of nephrotic syndrome (NS) that manifests in the first 3 months of life. They are rare diseases mainly due to genetic causes but sometimes attributed to congenital infections. The prognosis depends on the type of mutation in the former and whether remission occurs with specific therapy in the latter. Clinical Description: We describe an 11-week-old baby who presented with generalized edema and features of septic shock that responded to antibiotics. The presence of hypoalbuminemia, proteinuria, and hypercholesterolemia completed the clinical phenotype of NS. Mesangioproliferative glomerulonephritis was confirmed on histopathology. The presence of persistent hepatosplenomegaly, neurological findings, decreased head circumference, and poor nutritional status prompted us to investigate for congenital infections. Positive antibody levels for Cytomegalovirus (CMV) and positive polymerase chain reaction confirmed CMV infection, though we were unable to establish whether it was congenital or acquired postnatally. A novel genetic mutation (c. 712+1G>C) was identified in the NPHS 1 gene. Management: The baby was initiated on specific antiviral therapy and attained partial remission of renal symptoms after 4 weeks. The patient was lost to follow-up after 6 months. Conclusion: The coexistence of the Finnish variety and CMV infection might have caused the severity of phenotype. The authors emphasize the importance of performing a genetic test in cases of congenital NS and also working up for acquired causes on an individualized basis.